Synergistic electronic effects in AuCo nanoparticles stabilized in a triazine-based covalent organic framework: a catalyst for methyl orange and methylene blue reduction - Devulapalli, Venkata Swaroopa Datta; Kushwaha, Rinku; Ovalle, Edwin; Singh, Himan Dev; Shekhar, Pragalbh; Chakraborty, Debanjan; Vinod, Chathakudath Prabhakaran; Vaidhyanathan, Ramanathan; Borguet, Eric (ACS Applied Nano Materials, 2022)
Developing stable active catalysts for reducing water-soluble pollutants is a desirable target. In this pursuit, we have functionalized covalent organic frameworks (COFs) with gold (Au) and cobalt (Co) nanoparticles via a one-step aqueous synthesis process, and their catalytic activity in reducing methyl orange and methylene blue is examined. Operando absorbance measurements of methyl orange (anionic dye) reduction revealed AuCoCOF (1.3 Au/1.0 Co) to have superior kinetics over many other catalysts, which typically require additional external stimuli (e.g., photons) and higher catalyst loadings. After confirming the homogeneous dispersion of the nanoparticles on the COF support using three-dimensional (3D) tomography and material stability through powder X-ray diffraction (PXRD), infrared (IR), and thermal studies, we investigated their redox activity. Cyclic voltammetry (CV) confirmed the involvement of both metals in the redox process, while spectroelectrochemical measurements show that their activity and kinetics remain unaltered by an applied potential. Solid-state UV measurements reveal that the neat COF is a semiconductor with a large band gap (2.8 eV), which is substantially lowered when loaded with cobalt nanoparticles (2.2 eV for CoCOF). The electronic synergy between Au and Co nanoparticles further reduces the band gap of AuCoCOF (1.9 eV). Thus, there is a definite advantage in doping non-noble metal nanoparticles into a noble metal lattice and nanoconfining them into a porous COF support. Our study highlights the significance of bimetallic COF-supported nanocatalysts, wherein one can engage each component toward targeted applications that demand redox activity with favorable kinetics.
Keywords: AuCoCOF; band gaps; Covalent organic framework; methyl orange reduction; Nanoparticles; UV-vis spectroscopy

COF-supported zirconium oxyhydroxide as a versatile heterogeneous catalyst for Knoevenagel condensation and nerve agent hydrolysis - Shekhar, Pragalbh; Devulapalli, Venkata Swaroopa Datta; Reji, Reshma; Singh, Himan Dev; Jose, Aleena; Singh, Piyush; Torris, Arun; Vinod, Chatakudath P.; Tokarz III, John A.; Mahle, John J.; Peterson, Gregory W.; Borguet, Eric; et al. (iScience, 2023)
A composite of catalytic Lewis acidic zirconium oxyhydroxides (8 wt %) and a covalent organic framework (COF) was synthesized. X-ray diffraction and infrared (IR) spectroscopy reveal that COF's structure is pre-served after loading with zirconium oxyhydroxides. Electron microscopy confirms a homogeneous distri-bution of nano-to sub-micron-sized zirconium clusters in the COF. 3D X-ray tomography captures the micron-sized channels connecting the well-dispersed zirconium clusters on the COF. The crystalline ZrOx(OH)(y)@COF's nanostructure was model-optimized via simulated annealing methods. Using 0.8 mol % of the catalyst yielded a turnover number of 100-120 and a turnover frequency of 160-360 h(-1) for Knoevenagel condensation in aqueous medium. Additionally, 2.2 mol % of catalyst catalyzes the hy-drolysis of dimethyl nitrophenyl phosphate, a simulant of nerve agent Soman, with a conversion rate of 37% in 180 min. The hydrolytic detoxification of the live agent Soman is also achieved. Our study unveils COF-stabilized ZrOx(OH)(y) as a new class of zirconium-based Lewis + Bronsted-acid catalysts.